Ross Errilly Franciscan Friary, cloister, base - O'Donovan, Danielle (My University, 2008)
Cloister base, moulding comprises from top down: chamfered fillet as necking, ogee bell.
Cloister
Keywords: chamfered fillet; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Cloisters (Architecture); Late Medieval; moldings, ogee